Building-Integrated Photovoltaic Systems (BIPVS) Performance and Modeling Under Outdoor Conditions - Aristizábal Cardona, Andrés Julián (Springer International Publishing, 2018)
This book discusses building-integrated photovoltaic systems (BIPV) and provides solutions for solving problems related to designing, sizing and monitoring a BIPV that has been used to replace conventional building materials in parts of the building envelope such as the roof, skylights or facades. The book begins by introducing the basics to readers interested in learning about this technology and then outlines in an accessible way, a practical development plan for the installation and monitoring of these systems in residential, industrial, and commercial buildings. Chapters discuss the needs of installing, designing, and sizing and provide a financial analysis for a successful implementation of a BIPV system. This book is a useful tool for renewable energy designers, energy contractors, architects, government institutions, and those in the academic community who are interested in seamlessly integrating solar panels into the construction phase of new building projects or retrofitted into existing buildings.